Multiple Pain Generators and Central Amplification in Chronic Pain: A Narrative Review of Peripheral-Central Mechanism - Riyanto Sofyan, Henry (Departemen Neurologi Fakultas Kedokteran Universitas Indonesia, 2026)
Background:Chronic pain is increasingly recognized as a complex condition involving interactions between peripheral nociceptive sources and central nervous system amplification mechanisms. Traditional models that focus solely on tissue damage are inadequate to explain the persistence and widespread distribution of many chronic pain conditions. Methods:This narrative review synthesizes current theoretical frameworks and empirical evidence on how peripheral pain sources interact with central amplification mechanisms. Literature from clinical, experimental, and neurobiological studies was reviewed to explore mechanisms underlying central sensitization, neuroinflammation, and patterns of pain comorbidity. Results:Evidence suggests that central sensitization, marked by increased neuronal excitability in central pain pathways, is a key mechanism connecting various chronic pain conditions. Peripheral nociceptive inputs, such as tissue inflammation, nerve injury, and musculoskeletal problems, can trigger and maintain central sensitization. Neuroimmune interactions and changes in descending pain modulation also help amplify and sustain pain. Epidemiological studies show frequent overlap among chronic pain conditions, supporting the idea of shared mechanisms involving peripheral and central interactions. Conclusion:Chronic pain is best understood as the outcome of dynamic interactions between peripheral pain sources and central amplification mechanisms. Recognizing these bidirectional processes has vital implications for clinical assessment and multimodal treatment approaches. Future research should prioritize longitudinal studies, validated mechanistic biomarkers, and integrated models that encompass peripheral, central, and psychosocial factors. Keywords: chronic pain; central sensitization; pain generators; neuroinflammation; pain mechanisms